9
$\begingroup$

Here are the power series of sine and cosine: $$\sin(x) = \sum_{n=0}^{\infty} (-1)^n \frac {x^{2n+1}} {(2n+1)!}$$ and $$\cos(x) = \sum_{n=0}^{\infty} (-1)^n \frac {x^{2n}} {(2n)!}$$

How can it be proved that $(\sin x)^2 + (\cos x)^2 = 1$ using the Cauchy product formula?

Maybe somehow with the identity $$\sum_{k=0}^{m} (-1)^k\binom mk$$ which is zero?

$\endgroup$
  • $\begingroup$ Possibly relevant: $\sum_{k=0}^n \binom nk=2^n$, I think. $\endgroup$ – Akiva Weinberger Jan 22 '15 at 16:40
9
$\begingroup$

Just to see how ugly it is, you actually can do it using Cauchy products: \begin{align*}\cos^2 x&=\left(\sum_{n=0}^{\infty}(-1)^n\frac{x^{2n}}{(2n)!}\right)^{\!2}=\sum_{n=0}^\infty\sum_{k=0}^n (-1)^{n-k}\frac{x^{2(n-k)}}{(2(n-k))!}(-1)^k\frac{x^{2k}}{(2k)!}=\sum_{n=0}^\infty\sum_{k=0}^n(-1)^n\binom{2n}{2k}\frac{x^{2n}}{(2n)!}\\ \sin^2 x&=\left(\sum_{n=0}^{\infty}(-1)^n\frac{x^{2n+1}}{(2n+1)!}\right)^2=\sum_{n=0}^\infty\sum_{k=0}^n (-1)^{n-k}\frac{x^{2(n-k)+1}}{(2(n-k)+1)!}(-1)^k\frac{x^{2k+1}}{(2k+1)!}\\&=\sum_{n=0}^\infty\sum_{k=0}^n(-1)^n\binom{2n+2}{2k+1}\frac{x^{2n+2}}{(2n+2)!}=\sum_{n=1}^\infty\sum_{k=0}^{n-1}(-1)^{n-1}\binom{2n}{2k+1}\frac{x^{2n}}{(2n)!}\end{align*} Now utilize the binomial theorem: \begin{align*}\cos^2 x+\sin^2 x&=1+\sum_{n=1}^\infty(-1)^n\left(\sum_{k=0}^n\binom{2n}{2k}-\sum_{k=0}^{n-1}\binom{2n}{2k+1}\right)\frac{x^{2n}}{(2n)!}\\&=1+\sum_{n=1}^\infty(-1)^n\sum_{k=0}^{2n}(-1)^k\binom{2n}{k}\frac{x^{2n}}{(2n)!}=1+\sum_{n=1}^\infty(-1)^n(1-1)^{2n}\frac{x^{2n}}{(2n)!}=1+\sum_{n=0}^\infty 0\\&=1\end{align*}

$\endgroup$
3
$\begingroup$

This doesn't use the Cauchy product formula, but you can resolve this identity using the power series themselves.

Using the power series we find that $$\frac{d}{dx}\sin(x) = \cos(x)$$ and $$\frac{d}{dx} \cos(x) = -\sin(x).$$

Note also that: $$2\sin(x)\cos(x)-2\cos(x)\sin(x)=0$$

Integrating both sides gives us $$(\sin(x))^2 + (\cos(x))^2 = C$$ for some constant $C$. Finally we can determine $C$ by plugging in $x=0$. This gives us $(0)^2 + 1^2 = C$. Thus we can conclude that $$(\sin(x))^2+(\cos(x))^2=1.$$


As a side note you can also determine the power series for $f(x)=(\sin(x))^2$ as well as for $(\cos(x))^2$ without using the Cauchy formula.

Note that $f(0)=0$ and $$f'(x)=2\sin(x)\cos(x)=\sin(2x)=\sum_{n=0}^\infty \frac{(-1)^n2^{2n+1}x^{2n+1}}{(2n+1)!}$$ thus $$(\sin(x))^2 = \sum_{n=0}^\infty \frac{(-1)^n 2^{2n+1} x^{2n+2}}{(2n+2)!}.$$

$\endgroup$
0
$\begingroup$

Youcan just show that $\sin(x)=\dfrac{e^{ix}-e^{ix}}{2i}$ and $\cos(x)=\dfrac{e^{ix}+e^{ix}}{2}$ from the power series, and then square and add.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.